Professionalization of public health and training of sanitarians in Peru: 1935-1968 - Bustíos Romaní, Carlos (2018)
This article presents bibliographic and testimonials information about the history of the professionalization of public health, and the professional development of the sanitarians in Peru during the period between 1935 and 1968, in order to provide legitimacy to the comments that were made about the internal and external reasons of achievements and limitations of both process during, and at the end of this period. For this purpose, the article is organized into six sections: Background information of the region of the Americas and Peru; the professionalization of public health in Peru (1935-1968); Public health professional development and the foreign cooperation in Peru (1935-1968); the training programs for sanitarians in Peru (1961-1963); the School of Public Health of Peru (1964-1968); and, comments about the situation of the sanitarians in the sixties decade.